Characterisation of anifrolumab, a fully human anti-interferon receptor antagonist antibody for the treatment of systemic lupus erythematosus - Riggs, Jeffrey M; Hanna, Richard N; Rajan, Bhargavi; Zerrouki, Kamelia; Karnell, Jodi L; Sagar, Divya; Vainshtein, Inna; Farmer, Erika; Rosenthal, Kimberly; Morehouse, Chris; de los Reyes, Melissa; Schifferli, Kevin; et al. (Lupus science & medicine, 2018)
ObjectiveWe investigated the mechanistic and pharmacological properties of anifrolumab, a fully human, effector-null, anti-type I interferon (IFN) alpha receptor 1 (IFNAR1) monoclonal antibody in development for SLE.MethodsIFNAR1 surface expression and internalisation on human monocytes before and after exposure to anifrolumab were assessed using confocal microscopy and flow cytometry. The effects of anifrolumab on type I IFN pathway activation were assessed using signal transducer and activator of transcription 1 (STAT1) phosphorylation, IFN-stimulated response element–luciferase reporter cell assays and type I IFN gene signature induction. The ability of anifrolumab to inhibit plasmacytoid dendritic cell (pDC) function and plasma cell differentiation was assessed by flow cytometry and ELISA. Effector-null properties of anifrolumab were assessed in antibody-dependent cell-mediated cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC) assays with B cells.ResultsAnifrolumab reduced cell surface IFNAR1 by eliciting IFNAR1 internalisation. Anifrolumab blocked type I IFN-dependent STAT1 phosphorylation and IFN-dependent signalling induced by recombinant and pDC-derived type I IFNs and serum of patients with SLE . Anifrolumab suppressed type I IFN production by blocking the type I IFN autoamplification loop and inhibited proinflammatory cytokine induction and the upregulation of costimulatory molecules on stimulated pDCs. Blockade of IFNAR1 suppressed plasma cell differentiation in pDC/B cell co-cultures. Anifrolumab did not exhibit CDC or ADCC activity.ConclusionsAnifrolumab potently inhibits type I IFN-dependent signalling, including the type I IFN autoamplification loop, and is a promising therapeutic for patients with SLE and other diseases that exhibit chronic dysfunctional type I IFN signalling.